Short durations of corticosteroids for hospitalised COVID-19 patients are associated with a high readmission rate. Issue 6 (June 2021) - Chaudhry, Zain; Shawe-Taylor, Marianne; Rampling, Tommy; Cutfield, Tim; Bidwell, Gabriella; Chan, Xin Hui S.; Last, Anna; Williams, Bryan; Logan, Sarah; Marks, Michael; Esmail, Hanif
Summary: Objective: Our objective was to describe the characteristics of patients admitted, discharged and readmitted, due to COVID-19, to a central London acute-care hospital during the second peak, in particular in relation to corticosteroids use. Methods: We reviewed patients admitted from the community to University College Hospital (UCH) with COVID-19 as their primary diagnosis between 1st-31st December 2020. Re-attendance and readmission data were collected for patients who re-presented within 10 days following discharge. Data were retrospectively collected. Results: 196 patients were admitted from the community with a diagnosis of COVID-19 and discharged alive in December 2020. Corticosteroids were prescribed in hospital for a median of 5 days (IQR 3–8). 20 patients (10.2%) were readmitted within 10 days. 11/20 received corticosteroids in the first admission of which 10 had received 1–3 days of corticosteroids. Readmission rate in those receiving 1–3 days of corticosteroids was 25%. Conclusions: Most international guidelines have recommended providing up to 10 days of corticosteroids for severe COVID-19 but stopping on discharge. Our findings show shorter courses of corticosteroids during admission are associated with an increased risk of being readmitted and support continuing the course of corticosteroids after hospital discharge monitored in the virtual ward setting.